(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Due to the compounds’ affinity for mammalian systems, the Allium cepa assay is frequently employed to assess the antigenotoxicity of the substances. Mucilage was extracted from the leaves of Aegle marmelos and the fruits of Bridelia scandens for this investigation. The antigenotoxic potential of the mucilage at various concentrations was evaluated in comparison to pure water as a negative control and mercuric chloride as a positive control.